Implementation of Process Approach in Learning Write A Short Story - Siti Halidjah (Universitas Tanjungpura, 2018)
This study aims to gain an in-depth understanding of the implementation of a process approach in short story writing lessons to students of PGSD Study Program FKIP Untan. This research uses qualitative approach. Sources of data in this study is a short story writing learning event using a process approach. The research procedure used in this research is planning, execution, data analysis, and report writing. Data collecting technique used is direct observation technique and document observation. The data collection tools used are field notes and documentation pertaining to the learning process and learning outcomes. Analysis of this research data begins with data collection, data reduction, data presentation, and inference/verification. Based on the results and discussion in this study can be concluded that the process approach can improve students' writing short story skills. This increase can be seen from the process as well as the product. Learning to write by following the stages of the process approach can help the lecturer to provide variations and stimuli in the task of writing a given short story. The improvement process can be seen from the process of creative writing learning with process approach in student activities and class situation in creative writing poetry learning, while from the product side of the students' writing skill improvement skills.